Garlic (Allium sativum L.) chemical composition, antioxidant and antimicrobial activities, and in vitro effect on digestion in sheep - Sahli F.; Darej C.; Guesmi H.; Hamrouni L.; Moujahed N. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
An in vitro study also was conducted to evaluate the effect of garlic (Allium Sativum L.) powder (GaP) supplementation on rumen fermentation. Two successive 24 h-incubations were practiced. Growing doses of garlic powder were added to 500 mg of a diet composed (50% of rye-grass hay, 50% of concentrate on DM basis). pH, ammonia nitrogen (NH3-N) and true organic matter degradability (TOMD) were measured and partitioning factor (PF) and microbial biomass (MBM) were estimated. Results showed that garlic powder was low in ash (3.5% DM), relatively high in CP (16.6% DM) and very lowly lignified (ADL < 2.2 % DM). Colorimetric analysis revealed that total phenols, flavonoids and tannins contents were respectively 0.37 mg AG.eq, 0.11 mg EC and 30.2 mg EC /g DM. All aqueous extracts exhibited a high, concentration dependent, free radical-scavenging activity. It was found that all extracts exhibited antibacterial activity against Gram(–) (Escherichia coli) and Gram(+) bacteria (Staphylococcus aureus and Bacillus subtilis), but ethanol extract was proven to be more efficient against the Gram(–) bacteria. The in vitro trial results indicated that GaP (32 and 64 mg doses) increases significantly (P<0.001) gas production after 24 h. No effect on pH was observed. An increase (P<0.0001) in NH3-N concentration was recorded with 4 mg and 8 mg doses compared with control; whereas adding 32 and 64 mg resulted in a NH3-N concentration equivalent to control. Total VFA concentration noted with control (73.6 mmolL-1) was lower (P<0.001), compared to that noted from adding GaP (averaged 99.28 mmolL-1). The propionate (C3) increased with GaP, and the highest proportion was noted with the addition of 8 mg (P <0.001). The TOMD was similar for all the doses except for 64 mg GaP, where a slight but significant (P <0.001) increase was noted (77.7%). PF values were equivalent in all doses (averaged 3.2), while a significant (P<0.0001) increase (4.45) was noted with 64 mg. The same trend was observed in MBM (P <0.001). It was concluded that GaP present some advantages related to its antioxidant and antimicrobial actions and could be considered as a natural alternative to synthetic antioxidants. Also, it modified positively rumen fermentations. In vivo and performance and quality measurements are necessary to confirm the eventual positive benefits of garlic on ewes feeding.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)